The Methodology of Organizing Independent Work Based on a Credit – Modular System for the Study of Organic Chemistry (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study investigates the methodology of organizing independent work within a credit–modular system for teaching organic chemistry in higher education. While global adoption of the European Credit Transfer and Accumulation System (ECTS) has demonstrated success in promoting autonomy and competence-based learning, its application in Uzbekistan remains underexplored, especially in discipline-specific contexts like chemistry. Addressing this knowledge gap, the study develops and implements a modular educational program focused on hydrocarbons, integrating didactic goals, cognitive tasks, and self-assessment tools. The research method involves designing structured modules that include theoretical content, practical tasks, and guided self-study materials aligned with credit allocations. Findings reveal that modular instruction significantly enhances students' independent learning, critical thinking, and problem-solving skills. Results also show that systematic modularization supports gradual knowledge accumulation and improves educational outcomes through diversified assessment strategies. The implication of this work lies in demonstrating that the credit-modular system, when adapted effectively, can modernize chemistry education in Uzbekistan, foster academic mobility, and align with international standards. These insights support the need for teacher training, robust modular content, and culturally aware implementation strategies for sustainable educational reform.